Knowledge Management for Health Care Procedures From Knowledge to Global Care, AIME 2007 Workshop K4CARE 2007, Amsterdam, The Netherlands, July 7, 2007, Revised Selected Papers - Riano, David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
The incursion of information and communication technologies (ICT) in health care entails evident bene?ts at the levels of security and e?ciency that improve not only the quality of life of the patients, but also the quality of the work of the health care professionals and the costs of national health care systems. Leaving research approaches aside, the analysis of ICT in health care shows an evo- tion from the initial interest in representing and storing health care data (i. e. , electronic health care records) to the current interest of having remote access to electronic health care systems, as for example HL7 initiatives or telemedicine. This sometimes imperceptible evolution can be interpreted as a new step of the progress path of health care informatics, whose next emerging milestone is the convergenceof current solutions with formal methods for health care kno- edge management. In this sense, K4CARE is a European project aiming at contributing to this progress path. It is centered on the idea that health care knowledge rep- sented in a formal waymay favor the treatment of home care patients in modern societies. The project highlights several aspects that are considered relevant to the evolution of medical informatics: health care knowledge production, health care knowledge integration, update, and adaptation, and health care intelligent systems.
Health Care Knowledge Management -- Healthcare Knowledge Management: The Art of the Possible -- Health Care Knowledge Elicitation -- Using Lexical, Terminological and Ontological Resources for Entity Recognition Tasks in the Medical Domain -- Learning Medical Ontologies from the Web -- Mining Hospital Data to Learn SDA* Clinical Algorithms -- Generating Macro-Temporality in Timed Transition Diagrams -- Health Care Knowledge Transformation -- Automatic Combination of Formal Intervention Plans Using SDA* Representation Model -- The Data Abstraction Layer as Knowledge Provider for a Medical Multi-agent System -- Enlarging a Medical Actor Profile Ontology with New Care Units -- Health Care Knowledge-Based Intelligent Systems -- A Concept-Based Framework for Retrieving Evidence to Support Emergency Physician Decision Making at the Point of Care -- Decision Making System Based on Bayesian Network for an Agent Diagnosing Child Care Diseases -- PIESYS: A Patient Model-Based Intelligent System for Continuing Hypertension Management -- An Intelligent Platform to Provide Home Care Services.
Keywords: Artificial intelligence; Health informatics; Optical data processing; Application software; Data mining; Database management; Artificial Intelligence; Health Informatics; Image Processing and Computer Vision; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Database Management